Culture, Structure, Strategy and Power An investigation of organisational dynamics at Games Workshop - Dews, Robin Paul (2007)
At the core of this project is an examination of how Games Workshop has managed the integration-differentiation paradox over a fifteen to twenty-year period and how the strategies it has employed have impacted upon the culture, structure and performance of the business.